Synthesis of Biogenic silver nanoparticles using plant growth-promoting bacteria: Potential use as biocontrol agent against phytopathogens - Mittal, Divya; Kumar, Arun; Balasubramaniam, Bhuvaneshwari; Thakur, Rahul; Singh Siwal, Samarjeet; V. Saini, Reena; K. Gupta, Raju; K. Saini, Adesh (Biomaterials and Polymers Horizon, 2021)
Biogenic nanoparticles (NPs) derived from microbes present an excellent opportunity to deal with various challenges in medicine, diagnosis, environment and agriculture. In the area of agriculture sciences, researchers are facing challenges related to excessive utilization of pesticides which can be answered by utilizing plant growth-promoting (PGP) microbes. Herein, we have employed the culture filtrate of two PBP bacteria strains, Serratia marcescens and Burkholderia cepacia to prepare biogenic silver NPs. The biogenic silver NPs were characterized by various techniques viz. UV-VIS spectroscopy, SEM, XRD and FTIR. The biogenic AgNPs were able to control the growth of phytopathogenic fungi Aspergillus niger, A. fumigatus, Fusarium oxysporum, Pythium sp., and Rosellinia sp. by more than 80% as examined by in vitro growth reduction on agar medium. Very significantly, the growth inhibition of seedlings by phytopathogenic fungi was efficiently rescued using biogenic AgNPs derived from PGP bacteria. These results indicate the potential use of biogenic NPs to reduce the burden of chemical-based pesticides.